Antimicrobial Activity of NCR Plant Peptides Strongly Depends on the Test Assays - Farkas, Attila; Pap, Bernadett; Kondorosi, Éva; Maróti, Gergely (Frontiers in Microbiology, 2018)
The symbiosis specific NCR247 and NCR335 cationic plant peptides of Medicago truncatula have been shown to exert antimicrobial activity against a wide range of microbes. However, their antimicrobial efficiency is clearly limited by divalent cations. Here, the antibacterial and antifungal activities of NCR247 and NCR335 peptides were compared to those of the well-characterized peptide antibiotics polymyxin B and the aminoglycoside streptomycin on three model microbes, Escherichia coli, Bacillus subtilis and Saccharomyces cerevisiae as representatives of Gram-negative and Gram-positive bacteria as well as eukaryotic fungi. The aim of the study was to assess how the killing efficiency of these peptides depends on various, widely used antimicrobial susceptibility assays. Validated resazurin microdilution assay was used to determine minimal growth inhibitory concentrations in three general test media (MHB, MHBII and low-salt medium LSM). Bactericidal/fungicidal activities were determined by the commonly used drop plate assay. The natural plant peptides showed distinct characteristics, NCR247 had a generally high sensitivity for Ca2+ and Mg2+ in the medium, while NCR335 proved to be a robust and strong antimicrobial agent with comparable efficiency values to polymyxin B. Activity data were confirmed visually, both NCR247 and NCR335 treatments at minimal bactericidal concentrations induced complete disruption of the membranes and provoked cell lysis on all tested microorganisms as observed by scanning electron microscopy.